2021
DOI: 10.1007/s11239-021-02565-6
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 risk index (CRI): a simple and validated emergency department risk score that predicts mortality and the need for mechanical ventilation

Abstract: Although certain risk factors have been associated with morbidity and mortality, validated emergency department (ED) derived risk prediction models specific to coronavirus disease 2019 (COVID-19) are lacking. The objective of this study is to describe and externally validate the COVID-19 risk index (CRI). A large retrospective longitudinal cohort study was performed to analyze consecutively hospitalized patients with COVID-19. Multivariate regression using clinical data elements from the ED was used to create … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Patients on preadmission OAC had a higher prevalence of demographic and co-morbid characteristics associated with adverse outcomes during hospitalization for COVID-19. 14 , 15 Patients on preadmission OAC were older, more frequent tobacco users, more often Hispanic, and more likely to have a history of heart failure, myocardial infarction, TIA, stroke, DVT, PE, chronic kidney disease, and cancer, and were less likely to have a history of alcohol use disorder. These patients were also less likely to be taking aspirin or a P2Y 12 inhibitor, and more likely to be on a statin before admission when compared with those who were not taking OAC.…”
Section: Resultsmentioning
confidence: 99%
“…Patients on preadmission OAC had a higher prevalence of demographic and co-morbid characteristics associated with adverse outcomes during hospitalization for COVID-19. 14 , 15 Patients on preadmission OAC were older, more frequent tobacco users, more often Hispanic, and more likely to have a history of heart failure, myocardial infarction, TIA, stroke, DVT, PE, chronic kidney disease, and cancer, and were less likely to have a history of alcohol use disorder. These patients were also less likely to be taking aspirin or a P2Y 12 inhibitor, and more likely to be on a statin before admission when compared with those who were not taking OAC.…”
Section: Resultsmentioning
confidence: 99%
“…SpO 2 , a measure of oxygenation, and S/F, appeared infrequently in the models, which differs from previous studies that found S/F to be highly associated with the need for IMV or death; however, these studies did not separately analyse FiO 2 . 11 , 19 , 20 , 21 A rising FiO 2 should be taken as one of the warning signs for impending death or need for IMV. Vital signs, particularly, respiratory rate and temperature, were also commonly present in the models.…”
Section: Discussionmentioning
confidence: 99%
“…While several studies have attempted to develop a prediction model for the need of MV or ICU admission, there is no well-accepted method that captures rapidly changing respiratory status in patients with COVID-19 [ 7 12 ]. Although some clinical scoring systems showed promising results with high discrimination, most use daily clinical data or those on admission and only predict deterioration within 24–48 h or thereafter [ 8 , 9 , 11 , 12 ]. Since candidates for MV are usually on oxygen therapy and changes in respiratory status are frequently assessed within a day, estimation with such a long-term interval using a score is not practical.…”
Section: Introductionmentioning
confidence: 99%